Service to God, Service to Master/Client: African Indian Military Contribution in Karnataka - Obeng, Pashington (African and Asian studies, 2007)
Abstract This essay examines how African Indians (Abyssinians, Habshis, Siddis) from medieval times to the present have played significant political and military roles to forge sovereignties in the land area currently covered by the State of Karnataka, South India. I provide a brief history of the military activities of African Indians in the Indian subcontinent to foreground how the Africans deployed the unstable political climate in the Deccan, ethnicization of military culture, religious filiation, and force of personality to assert influence over communities that settled in areas bounded by present-day Karnataka.